2021
DOI: 10.3389/fphar.2021.707399
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidine Attenuates Heart Failure by Improving Myocardial Metabolism via AMPK

Abstract: Energic deficiency of cardiomyocytes is a dominant cause of heart failure. An antianginal agent, trimetazidine improves the myocardial energetic supply. We presumed that trimetazidine protects the cardiomyocytes from the pressure overload-induced heart failure through improving the myocardial metabolism. C57BL/6 mice were subjected to transverse aortic constriction (TAC). After 4 weeks of TAC, heart failure was observed in mice manifested by an increased left ventricular (LV) chamber dimension, an impaired LV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The mice were anaesthetised and subjected to sham or TAC surgery with a 27‐gauge needle and 7–0 silk suture as described previously. 15 Mice in the sham group and the TAC group were provided by Vehicle, PFD (300 mg/kg/day) 16 and CAP (20 mg/kg/day), 7 respectively. Vehicle, PFD, and CAP were intragastric administrated with an equal volume (200 μl).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mice were anaesthetised and subjected to sham or TAC surgery with a 27‐gauge needle and 7–0 silk suture as described previously. 15 Mice in the sham group and the TAC group were provided by Vehicle, PFD (300 mg/kg/day) 16 and CAP (20 mg/kg/day), 7 respectively. Vehicle, PFD, and CAP were intragastric administrated with an equal volume (200 μl).…”
Section: Methodsmentioning
confidence: 99%
“…After 1 week of adaptive feeding, the mice were randomly divided into six groups: Sham group, PFD group, CAP group, TAC group, TAC + PFD group, TAC + CAP group. The mice were anaesthetised and subjected to sham or TAC surgery with a 27‐gauge needle and 7–0 silk suture as described previously 15 . Mice in the sham group and the TAC group were provided by Vehicle, PFD (300 mg/kg/day) 16 and CAP (20 mg/kg/day), 7 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the abnormality of the structure and function of mitochondria in the pressure overload model has been frequently investigated. In vivo and in vitro experiments have confirmed that mitochondria swell and cristae become fragmented and disordered in cardiomyocytes under pressure overload [ 7 , 8 ]. Mitophagy is a selective autophagy pathway that mediates mitochondrial quality control by scavenging damaged mitochondria and coordinating the dynamic balance between mitochondrial and cellular energy requirements [ 9 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that this drug is the only cardioprotector included in the protocols for the treatment of patients with CVD, both by the Russian Society of Cardiology and the European Council of Cardiology [12,13]. TMZ inhibits the mitochondrial 3-ketoacyl-CoA thiolase, improves myocardial metabolism through enhancing the activation of AMPK, and thus improves insulin sensitivity and resultantly relived mitochondrial dysfunction [14,15].…”
Section:  Introductionmentioning
confidence: 99%